What drives the intention of Bavarian crafts apprentices to change employer or occupation? An empirical study in the crafts sector - Robert Wagner; Maximilian Wolf (Journal for Labour Market Research, 2013)
This paper combines several job related factors such as occupational enjoyment, job security, financial attractiveness, working conditions and social relations for the first time and estimates their impact on the intention of crafts apprentices to leave their training establishment or occupation. In contrast to previous analyses, we consider the dimension of the intended change by taking into account whether crafts apprentices intend to change establishment and/or occupation. We find that occupational enjoyment, regional proximity to the employer and job security are the most important drivers for the intention to stay with the training establishment. In contrast to other studies, monetary incentives do not drive the intention to leave the training establishment or occupation. Our results have far reaching implications for training establishments and institutions in the Bavarian crafts sector concerning incentive systems, initial screening of apprentices, further training as well as improvement of the image of the crafts sector to the public through crafts chambers.
Keywords: 330; Auszubildende; Handwerksberufe; Berufswechsel; Arbeitsplatzwechsel; zwischenbetriebliche Mobilität; Arbeitszufriedenheit; Arbeitsplatzsicherheit; soziale Beziehungen; Arbeitsweg; Ausbildungsbetrieb; Handwerk; Berufswegplanung; Ausbildungsabschluss; Bayern; Bundesrepublik Deutschland